(untitled) (Bioscience Journal, 2022)
The production of passion fruit is important in Brazil. In order to contribute to the development of the most promising cultivars of passion fruit, this study aimed to evaluate the agronomic performance of 32 genotypes of passion fruit in Federal District of Brazil, and to estimate genetic parameters for use in breeding programs. Thirty-two genotypes were used in a randomized block design, with eight plants per plot and four replications. The experiment was conducted in field. Twenty-eight harvests were performed, and the variables analyzed were: productivity estimated, total number of fruits per hectare, average fruit weight and these characteristics following classification of fruits in five categories. The genotypes that presented the highest total yield estimated were MAR20 # 23, AR 01 and PLANTA 7. For industrial purposes, genotypes MAR 20 # 21 and BRS Gigante Amarelo were superior. For fresh consumption, the genotypes with the best performance were PLANT 7, AR 01 and MSC. Total productivity estimated and total number of fruits per hectare in the first-class classification showed high values of heritability and CVg/CVe ratio. These results indicate a favorable condition for selection.